Respuesta :
Answer:
ST is two times MT
Step-by-step explanation:
we know that
ST=SM+MT -----> equation A (by addition segment postulate)
If m is the midpoint of ST
then
SM=MT -----> equation B
Substitute equation B in equation A
ST=(MT)+MT
ST=2MT
therefore
ST is two times MT
Answer:
[tex]2 \text{MT} = \text{ST}[/tex] OR
[tex]\text{MT}=\frac{1}{2} \text{ST}[/tex]
Step-by-step explanation:
We have, [tex]\text{M}[/tex] is the mid point of [tex]\text{ST}[/tex].
We know that a mid point divides a line segment into two equal parts.
So, [tex]\text{SM} = \text{MT}[/tex]
Also, [tex]\text{M}[/tex] is the point on line segment [tex]\text{ST}[/tex].
So, [tex]\text{SM} + \text{MT} = \text{ST}[/tex]
Now, substituting [tex]\text{MT}[/tex] in place of [tex]\text{SM}[/tex]
We get,
[tex]\text{MT} + \text{MT} = \text{ST}[/tex]
[tex]2 \text{MT} = \text{ST}[/tex]
OR
[tex]\text{MT}=\frac{1}{2} \text{ST}[/tex]